Photocatalytic Activity Enhancement of Anatase TiO2 by Using TiO. (16th March 2014) - Chen, Zhenrui; Zhong, Wei; Liang, Zhutian; Li, Weiqian; He, Guannan; Wang, Yinzhen; Li, Wei; Xie, Yuandong; He, Qinyu
Abstract : We employed high-energy ball-milling technique to fabricate TiO/TiO 2 heterogeneous nanostructures. XRD proved the existence of TiO/TiO 2 heterogeneous structures. SEM and HRTEM investigation evidenced that the mean particle size and mean grain size of the as-prepared samples are 23 nm and 13 nm, respectively. UV-Vis spectra exhibited that TiO has enhanced the visible light absorption of TiO 2 and has changed the E g of TiO 2 . UPS examination indicated that the electron work function (EWF) of TiO is higher than that of TiO 2 . Photocatalytic degradation experiments revealed that an appropriate TiO content can enhance the photocatalytic activity of pure anatase TiO 2 . The best photocatalytic activity of TiO/TiO 2 heterogeneous nanostructures is even better than that of Au-deposited TiO 2 by keeping high degradation efficiency of 93%. The internal electrical field producing in TiO/TiO 2 heterogeneous nanostructures was considered to be dominantly responsible for the enhanced photocatalytic activity. Therefore, the substitution of TiO with noble metal in TiO 2 will be widely used in the future due to its low cost. This study also provides a clear direction of enhancing photocatalytic activity of TiO 2 : incorporating a guest compound into TiO 2 with an appropriate content if the compound has much higher electron work function than that of TiO 2 .